The Impact of Motivation on Environmental Performance Through Pro Environmental Behavior Among Employees of Five-Star Hotels in East Kalimantan - Rizqy Anwar Hidayatullah; Bay La Ati; Hafidz Uddin Hidayat; Fenty Fauziah (IECON: International Economics and Business Conference, 2025)
This study aims to analyze the impact of intrinsic and extrinsic motivation on environmental performance through pro-environmental behavior among employees of five-star hotels in East Kalimantan. The research is motivated by the importance of implementing green human resource management (GHRM) practices to support sustainable development, especially in rapidly developing regions such as the future National Capital (IKN), which emphasizes the concept of a green city. The research object consists of 114 randomly selected employees from five-star hotels in East Kalimantan. The study uses a quantitative approach with survey methods, and data analysis is conducted using Partial Least Square Structural Equation Modeling (PLS-SEM) via the SmartPLS program. The results indicate that intrinsic motivation has a positive and significant effect on environmental performance (p=0.008), while extrinsic motivation does not have a significant effect (p=0.967). Pro-environmental behavior also has a positive and significant effect on environmental performance (p=0.000). The R-square value for environmental performance is 0.441, meaning that 44.1% of the variation in environmental performance can be explained by intrinsic motivation, extrinsic motivation, and pro-environmental behavior. These findings suggest that developing intrinsic motivation and promoting pro-environmental behavior are key strategies for enhancing organizational environmental performance. The discussion highlights the importance of intrinsic motivation in encouraging employee initiative and commitment to pro-environmental practices, while extrinsic motivation needs to be structured more effectively to be impactful. The study recommends that hotel management pay more attention to developing intrinsic motivation through training, recognition, and self-development opportunities, as well as implementing GHRM practices oriented toward environmental sustainability. Future research can expand the research variables and increase the sample size to strengthen the generalization of the findings.